The Intersection of Technology and Environmental Science: A Study of Satellite Sensing - Shaikh Heena; Kazi Kutubuddin Sayyad Liyakat (International Journal of Atmosphere, 2025)
As coastal communities continue to deal with the many threats that climate change brings, satellite sensing is becoming an increasingly vital tool for assessing and managing risk. By using this technology, environmental scientists, lawmakers, and city planners can make better choices that will make coastal cities safer and stronger in the long run. Using satellite data in city planning and disaster preparedness has made a big difference in lessening the effects of extreme weather, environmental damage, and rising sea levels. Satellite data has made this possible. Not only are resilience and adaptability options, they are also necessities. Satellite sensing makes it possible to achieve both of these goals successfully. There has been a revolution in how we keep an eye on sea levels thanks to satellite sensors. This technology gives us important information that helps us understand how climate change affects sea levels around the planet. As technology gets better, satellite observations will become more and more important for helping vulnerable people all around the world and supporting climate resilience measures. The use of cutting-edge sensing technologies, teamwork, and easier access to data are all helping to start a new age in environmental monitoring. All of these things are important for the future of our planet.
Keywords: Climate change; Satellite Sensing; Sea level; coastal areas; environmental study